Lithium-ion batteries and electronic devices
The introduction of a cyclic sulfonate ester-based electrolyte in lithium-ion batteries addresses the safety risks associated with gas generation by forming a protective CEI film on the positive electrode, thereby enhancing the safety and performance of the batteries.
Patent Information
- Application Number
- JP2024557648
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-29
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2042-03-29
AI Technical Summary
Lithium-ion batteries face safety risks due to the generation of gaseous by-products from side reactions, which can lead to increased pressure and potential hazards during use or transport.
The use of a lithium-ion battery electrolyte that includes a cyclic sulfonate ester, specifically a compound of formula (I) other than 1,3-propanesultone, which undergoes a reductive ring-opening reaction to form a protective CEI film on the positive electrode active material, reducing the risk of side reactions and gas generation.
The proposed electrolyte composition effectively reduces the amount of gas generated in lithium-ion batteries, enhancing safety characteristics by providing a protective layer for the positive electrode active material and improving the stability and cycle life of the battery.
Smart Images

Figure 2025510350000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of energy storage technology, and in particular to lithium-ion batteries and electronic devices. [Background technology]
[0002] Lithium-ion batteries have been widely used in electronic products such as mobile phones, laptops, and cameras due to their characteristics of high energy density, high operating voltage, and light weight. While the electrochemical properties of lithium-ion batteries have been improved, their safety characteristics cannot be ignored. During the use or transportation of lithium-ion batteries, side reactions may occur inside the lithium-ion batteries, resulting in the generation of gaseous by-products, which may cause the pressure inside the lithium-ion batteries to become too high, resulting in safety risks for the lithium-ion batteries.
[0003] Research has revealed that an electrolyte can undergo an interface reaction with a positive electrode active material and a negative electrode active material, and the interface reaction has a significant effect on the electrochemical properties and structural stability of the positive electrode material and the negative electrode material, and can reduce the amount of gas generation to a certain extent. However, at present, the protective effect of the electrolyte on the positive electrode active material and the negative electrode active material, especially the positive electrode active material, is still insufficient, so there is an urgent need to develop an electrolyte that can effectively protect the active material and thereby improve the safety characteristics of lithium-ion batteries. Summary of the Invention
[0004] The present invention provides a lithium ion battery and an electronic device that can improve safety characteristics by reducing the amount of gas generation in the lithium ion battery.
[0005] In a first aspect, the present invention proposes a lithium ion battery including a negative electrode, a positive electrode, a separator, and an electrolyte. The positive electrode includes a positive electrode active material. The separator is provided between the negative electrode and the positive electrode. The electrolyte includes a cyclic sulfonate ester, the cyclic sulfonate ester including 1,3-propane sultone and a compound represented by formula (I) other than 1,3-propane sultone. [ka] In formula (I), R 11 is selected from a substituted or unsubstituted C1-C4 alkylene group, and a substituted or unsubstituted C2-C4 alkenylene group; R 12 is a covalent bond, a substituted or unsubstituted C1-C2 alkyleneoxy group, -O-, and -R 13 -SO2-R 14 - selected from R 13 is selected from substituted or unsubstituted C1-C2 alkylene groups; R 14 is selected from a single covalent bond, a substituted or unsubstituted C1-C2 alkylene group, and -O-; R 11 , R 12 , R 13 and R 14 When at least one of the substituents is substituted, the substituents are C1-C 20 Alkyl groups, C6-C 30 an aryl group, a halogen atom, or -CN; Based on the mass n of the electrolyte, the content of the compound represented by formula (I) is A2%, and the value of A2 is in the range of 0.5-5.
[0006] In some embodiments of the present invention, the compound of formula (I) is a compound of formula (IA) or a compound of formula (IB): [ka] Here, R 61 , R 62 , and R 63are each independently selected from a hydrogen atom, a halogen atom, and a C1-C2 alkyl group.
[0007] In some embodiments of the present invention, the compound represented by formula (IA) is any one of the compounds represented by formulas (I-A1) to (I-A4). [ka]
[0008] In some embodiments of the invention, the compound of formula (IB) is a compound of formula (I-B1) or a compound of formula (I-B2). [ka]
[0009] In some embodiments of the present invention, the compound of formula (I) is a compound of formula (IC), a compound of formula (ID), or a compound of formula (IE): [ka] Here, R 71 , R 72 , and R 73 are each independently selected from a hydrogen atom, a halogen atom, and a C1-C2 alkyl group, and R 71 , R 72 , and R 73 and cannot simultaneously be hydrogen atoms.
[0010] In some embodiments of the present invention, the compound represented by formula (IC) is one of the compounds represented by formulae (I-C1) to (I-C5). [ka]
[0011] In some embodiments of the present invention, the compound of formula (ID) is a compound of formula (I-D1). [ka]
[0012] In some embodiments of the present invention, the compound of formula (IE) is a compound of formula (I-E1). [ka]
[0013] In some embodiments of the present invention, based on the mass n of the electrolyte, the mass of 1,3-propane sultone is A1, and the mass A1 of 1,3-propane sultone and the mass A2 of the compound represented by formula (I) satisfy 0.5≦A2 / A1≦8.0.
[0014] In some embodiments of the present invention, the mass n of the electrolyte and the mass m of the lithium ion battery satisfy 7%≦n / m≦15%, and optionally satisfy 10≦n / m≦15. Based on the mass n of the electrolyte, the mass of 1,3-propane sultone is A1, and the mass A1 of the 1,3-propane sultone and the mass m of the lithium ion battery satisfy 0.01%≦A1 / m≦0.1%.
[0015] In some embodiments of the present invention, the electrolyte further comprises a carboxylic acid ester additive. Based on the mass n of the electrolyte, the mass percentage y of the carboxylic acid ester additive is 5%≦y≦60%, and the mass percentage y of the carboxylic acid ester additive, the mass A1 of 1,3-propane sultone, and the mass A2 of the compound represented by formula (I) satisfy 0.05≦(A1+A2) / (n×y)≦0.6, and optionally satisfy 0.1≦(A1+A2) / (n×y)≦0.3.
[0016] In some embodiments of the present invention, the carboxylic acid ester additive comprises one or more of ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate, butyl propionate, ethyl difluoroacetate, and ethyl trifluoroacetate.
[0017] In some embodiments of the present invention, the electrolyte further comprises a carbonate-based additive. The carbonate-based additive comprises fluoroethylene carbonate and / or vinylene carbonate. Based on the mass n of the electrolyte, the mass percentage z of the carbonate-based additive is 0.5%≦z≦15%, and the mass percentage z of the carbonate-based additive, the mass A1 of the 1,3-propane sultone, and the mass A2 of the compound represented by formula (I) satisfy 0.1≦(A1+A2) / (n×z)≦7, and optionally satisfy 0.2≦(A1+A2) / (n×z)≦1.1.
[0018] In some embodiments of the present invention, the electrolyte further comprises a polynitrile additive, which is used to complex with cations in the positive electrode active material during charging and discharging of the lithium ion battery. Based on the mass n of the electrolyte, the mass percentage r of the polynitrile additive is 0.1%≦r≦12%, and optionally 0.5%≦r≦8%.
[0019] The polynitrile additive for the lithium ion battery contains one or more of the compounds represented by formulas (II-1) to (II-4), [ka] In formulas (II-1) to (II-4), R 21 is a substituted or unsubstituted C1-C 12 Alkylene groups, and substituted or unsubstituted C1-C 12 alkyleneoxy groups, R 31 , R 32 each independently represents a single covalent bond and a substituted or unsubstituted C-C 12 alkylene groups, R 41 , R 42 , and R 43 each independently represents a single covalent bond, a substituted or unsubstituted C-C 12 Alkylene groups, and substituted or unsubstituted C1-C 12 alkyleneoxy groups, R 51 is a substituted or unsubstituted C1-C 12 Alkylene groups, substituted or unsubstituted C2-C 12 Alkenylene groups, substituted or unsubstituted C6-C 26 Arylene groups, and substituted or unsubstituted C2-C 12 heterocyclylene groups, Here, R 21 , R 31 , R 32 , R 41 , R 42 , R 43 , and R 51 When at least one of is substituted, the substituent is a halogen atom.
[0020] In some embodiments of the present invention, the negative electrode, the separator, and the positive electrode are wound along a winding direction to form a wound structure, and the wound structure includes two ends facing each other along the winding direction and a middle portion located between the two ends, and the lithium ion battery further includes a case and a connection layer, in which an electrolyte and the wound structure are provided, and the connection layer includes a first surface and a second surface facing each other along its thickness direction, and the first surface connects the middle portion and the end of the two ends that is closer to the case, and the second surface connects to the case.
[0021] In some embodiments of the present invention, the connecting layer is a hot melt adhesive layer or a composite film layer including a hot melt adhesive layer.
[0022] In some embodiments of the present invention, the material of the hot melt adhesive layer comprises one or more of polyolefins, polyolefin copolymers, polyamides, polyurethanes, and epoxy resins.
[0023] In some embodiments of the present invention, the polyolefin comprises polyethylene and / or polypropylene, and the polyolefin copolymer comprises one or more of ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, styrene-isoprene-styrene copolymer, styrene-butadiene-styrene copolymer, styrene-(ethylene-butylene)-styrene copolymer, and styrene-(ethylene-propylene)-styrene copolymer.
[0024] In a second aspect, the present invention provides an electronic device comprising a lithium ion battery according to any embodiment of the first aspect of the present invention.
[0025] According to the electrolyte solution provided in the embodiment of the present invention, the electrolyte solution includes 1,3-propane sultone and a compound represented by formula (I). Both of the two compounds can undergo a reductive ring-opening reaction on the surface of the positive electrode active material, so as to stably form a CEI film layer on the surface of the positive electrode active material, and the CEI film layer can play a protective role on the positive electrode active material, thereby reducing the risk of side reactions between the positive electrode active material and other substances in the electrolyte, and thus reducing the risk of gaseous by-products being generated when side reactions occur. In addition, the mass A2 of the compound represented by formula (I) satisfies 0.5%≦A2 / n≦5%, and 1,3-propane sultone and the compound represented by formula (I) can exert a synergistic effect, forming a dense CEI film layer on the surface of the positive electrode active material, thereby further enhancing the protective role on the positive electrode active material. [Brief description of the drawings]
[0026] In the following, in order to explain the embodiments of the present invention, the necessary drawings for explaining the embodiments of the present invention or the prior art will be described briefly. Obviously, the drawings described below are only a part of the embodiments of the present invention. Those skilled in the art can still obtain drawings of other embodiments from the structures illustrated in these drawings without creative labor. [Figure 1]FIG. 1 is a schematic structural diagram of a lithium-ion battery provided in some embodiments of the present invention. [Diagram 2] FIG. 2 is a schematic structural diagram of a combination of the winding structure and the connecting layer of the lithium ion battery shown in FIG. [Diagram 3] 3 is a schematic structural diagram of an electronic device provided in some embodiments of the present invention. The drawing is not drawn to scale. Here, the reference numerals in the drawing are as follows: 1 Lithium-ion battery 11 Connection layer 12 Case 13 Winding structure; 131 End; 132 Middle part 10 Electronic device DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] Hereinafter, the embodiments of the present invention will be described in detail. In the entire specification of the present invention, the same or similar components and components having the same or similar functions are denoted by the same reference numerals. The embodiments related to the drawings described herein are illustrative and schematic and are used to provide a basic understanding of the present invention. The embodiments of the present invention should not be construed as limiting the present invention.
[0028] It should be noted that quantities, ratios, and other numerical values may be presented in a range format herein. Such range formats are used for convenience and brevity and are to be understood as including not only the explicit numerical values specified in the range limits, but also all individual numerical values or subranges within the range, as if each numerical value and subrange were explicitly set forth.
[0029] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "one or more of," or other similar terms can refer to any combination of the listed items. For example, if item A and item B are listed, the short phrase "at least one of A and B" means A only, B only, or A and B. In another example, if items A, B, and C are listed, the short phrase "at least one of A, B, and C" means A only, B only, C only, A and B (excluding C), A and C (excluding B), B and C (excluding A), or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0030] The term "alkyl group" includes straight chain and branched alkyl groups. For example, alkyl groups include C1-C 50 Alkyl groups, C1-C 40 Alkyl groups, C1-C 30 Alkyl groups, C1-C 20 Alkyl groups, C1-C 12 Alkyl groups, C1-C 10 The alkyl group can be an alkyl group, a C1-C6 alkyl group, or a C1-C4 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a tert-butyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, and the like. The alkyl group can be optionally substituted.
[0031] The term "alkylene group" refers to a group formed by the loss of two hydrogen atoms from the same carbon of an alkane or one hydrogen atom each from two different carbons. For example, an alkylene group is a C1-C 50 Alkylene groups, C1-C 40 Alkylene groups, C1-C 30 Alkylene groups, C1-C 20Alkylene groups, C1-C 12 Alkylene groups, C1-C 10 It can be an alkylene group, a C1-C6 alkylene group, or a C1-C4 alkylene group. In some embodiments, the alkylene group includes a methylene group -CH2-, an ethylene group, a 1,2-ethylene group, a propylene group, a 1,2-propylene group, a butylene group, a 1,2-butylene group, a 1,3-butylene group, a 1,4-butylene group, a pentylene group, a 1,2-pentylene group, and the like. In addition, the alkylene group may be optionally substituted.
[0032] The term "alkenyl group" includes straight-chain and branched alkenyl groups. For example, an alkenyl group can be any of C2-C 50 Alkenyl groups, C2-C 40 Alkenyl groups, C2-C 30 Alkenyl groups, C2-C 20 Alkenyl groups, C2-C 12 Alkenyl groups, C2-C 10 The alkenyl group can be a C2-C6 alkenyl group, a C2-C6 alkenyl group, or a C2-C4 alkenyl group. In some embodiments, the alkenyl group includes a vinyl group, a propenyl group, a butenyl group, a pentenyl group, a hexenyl group, a heptenyl group, an octenyl group, and the like. Additionally, the alkenyl group can be optionally substituted.
[0033] The term "alkenylene group" refers to a group that has lost a hydrogen atom from a carbon of an alkene. For example, an alkenylene group is a C-C 50 Alkenylene group, C2-C 40 Alkenylene group, C2-C 30 Alkenylene group, C2-C 20 Alkenylene group, C2-C 12 Alkenylene group, C2-C 10It can be an alkenylene group, a C2-C6 alkenylene group, a C2-C6 alkenylene group, or a C2-C4 alkenylene group. In some embodiments, the alkenylene group includes a vinylene group, a propenylene group, a butenylene group, a pentenylene group, a hexenylene group, a heptenylene group, an octenylene group, and the like. In addition, the alkenylene group may be optionally substituted.
[0034] The term "alkyleneoxy group" refers to a group consisting of an alkyl group that has lost a hydrogen atom and an oxygen atom. For example, an alkyleneoxy group is a C1-C 50 Alkyleneoxy groups, C1-C 40 Alkyleneoxy groups, C1-C 30 Alkyleneoxy groups, C1-C 20 Alkyleneoxy groups, C1-C 12 Alkyleneoxy groups, C1-C 10 The alkyleneoxy group may be an alkyleneoxy group, a C1-C6 alkyleneoxy group, a C1-C4 alkyleneoxy group, or a C1-C2 alkyleneoxy group. In some embodiments, the alkyleneoxy group includes a methyleneoxy group, an ethyleneoxy group, a propyleneoxy group, and the like. In addition, the alkyleneoxy group may be optionally substituted.
[0035] The term "aryl group" refers to a closed aromatic ring or ring system. For example, an aryl group can be any of C6-C 50 Aryl groups, C6-C 40 Aryl groups, C6-C 30 Aryl groups, C6-C 20 Aryl groups, C6-C 10 It can be an aryl group, for example, C6-C 30 An aryl group refers to a group containing 6 to 30 carbon atoms forming a ring. In some embodiments, aryl groups include phenyl, naphthyl, phenanthryl, anthryl, biphenyl, triphenylene, pyrenyl, spirobifluorenyl, perylenyl, indenyl, and azulenyl groups.
[0036] The term "halogen atom" refers to fluorine, chlorine, bromine atoms, and the like.
[0037] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In each embodiment, "hydrogen" can be 1H (protium, H).
[0038] Throughout this specification, substituents of compounds are disclosed in groups or in ranges, and all subcombinations of the members of such groups and ranges are specifically contemplated as being included in the invention. For example, the term "C1-C8 alkyl group" is specifically anticipated to disclose each of the C1, C2, C3, C4, C5, C6, C7, C8, C1-C8, C1-C7, C1-C6, C1-C5, C1-C4, C1-C3, C1-C2, C2-C8, C2-C7, C2-C6, C2-C5, C2-C4, C2-C3, C3-C8, C3-C7, C3-C6, C3-C5, C3-C4, C4-C8, C4-C7, C4-C6, C4-C5, C5-C8, C5-C7, C5-C6, C6-C8, C6-C7, and C7-C8 alkyl groups.
[0039] As another illustrative example, an integer range of 5 to 40 is specifically anticipated to disclose each of 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, and 40. An integer range of 1 to 20 is specifically anticipated to disclose each of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20. Other groups or ranges can be specifically anticipated based on this.
[0040] When the groups are substituted, the substituents are independently selected from alkyl groups, aryl groups, halogen atoms, cyano groups -CN, and combinations thereof.
[0041] In a high-temperature environment or during charge-discharge cycles, the positive electrode active material contained in a lithium-ion battery may crack irreversibly. After the positive electrode active material cracks, a new crystal surface is exposed. When the exposed crystal surface comes into contact with the electrolyte, the crystal surface and the electrolyte undergo a side reaction, producing gaseous by-products. The gaseous by-products increase the gas pressure inside the lithium-ion battery, thus posing a safety risk to the lithium-ion battery.
[0042] In view of this, the present invention designs the composition of the electrolyte from the viewpoint of protecting the positive electrode active material. A positive electrode protection additive such as a cyclic sulfonate ester is added to the electrolyte to form a cathode electrolyte interphase (CEI) film on the surface of the positive electrode active material, and the amount of the cyclic sulfonate ester used is adjusted to reduce the risk of side reactions occurring between the positive electrode active material and the electrolyte. Next, the technical solution of the present invention will be described in detail.
[0043] In a first aspect, the present invention proposes a lithium-ion battery.
[0044] As shown in Fig. 1, the lithium ion battery 1 includes a negative electrode, a positive electrode, a separator, and an electrolyte. The positive electrode includes a positive electrode active material. The separator is provided between the negative electrode and the positive electrode. The electrolyte includes a cyclic sulfonate ester, and the cyclic sulfonate ester includes 1,3-propane sultone (PS) and a compound represented by formula (I) other than 1,3-propane sultone. [ka] In formula (I), R 11 is selected from a substituted or unsubstituted C1-C4 alkylene group, and a substituted or unsubstituted C2-C4 alkenylene group; R 12 is a covalent bond, a substituted or unsubstituted C1-C2 alkyleneoxy group, -O-, and -R 13 -SO2-R 14 - selected from R 13is selected from substituted or unsubstituted C1-C2 alkylene groups; R 14 is selected from a single covalent bond, a substituted or unsubstituted C1-C2 alkylene group, and -O-; R 11 , R 12 , R 13 , and R 14 When at least one of the groups is substituted, the substituents are C1-C 20 Alkyl groups, C6-C 30 an aryl group, a halogen atom, or -CN; Here, the cyclic sulfonate ester is used to cause a reductive ring-opening reaction on the surface of the positive electrode active material during charging and discharging of the lithium ion battery 1, Based on the mass n of the electrolyte, the mass A2 of the compound represented by formula (I) satisfies 0.5%≦A2 / n≦5%.
[0045] According to the electrolyte of the embodiment of the present invention, both 1,3-propane sultone and the compound represented by formula (I) can undergo a reductive ring-opening reaction on the surface of the positive electrode active material, so as to stably form a CEI film layer on the surface of the positive electrode active material. The CEI film layer can protect the positive electrode active material, thereby reducing the risk of side reactions between the positive electrode active material and other substances in the electrolyte, and thus reducing the risk of gaseous by-products being generated when side reactions occur. In addition, the mass A2 of the compound represented by formula (I) satisfies 0.5%≦A2 / n≦5%. 1,3-propane sultone and the compound represented by formula (I) can exert a synergistic effect, forming a dense CEI film layer on the surface of the positive electrode active material, thereby further enhancing the protective effect on the positive electrode active material.
[0046] In some embodiments, the compound of formula (I) can include a compound of formula (IA): [ka] Here, R 61 , R 62are each independently selected from a hydrogen atom, a halogen atom, and a C1-C2 alkyl group. The halogen atom may be a fluorine atom or a chlorine atom, particularly a fluorine atom. The electric potential of a fluorine atom is relatively high, which is more advantageous for a film formation reaction.
[0047] Exemplarily, the compound represented by formula (IA) is any one of the compounds represented by formulas (I-A1) to (I-A4). [ka]
[0048] In some alternative embodiments, the compound of formula (I) can include a compound of formula (IB): [ka] Here, R 61 , R 62 , and R 63 are each independently selected from a hydrogen atom, a halogen atom, and a C1-C2 alkyl group.
[0049] Exemplarily, the compound represented by formula (IB) is a compound represented by formula (I-B1) or a compound represented by formula (I-B2). [ka]
[0050] In some further embodiments, the compound of formula (I) can include a compound of formula (IC): [ka] Here, R 71 , R 72 , and R 73 are each independently selected from a hydrogen atom, a halogen atom, and a C1-C2 alkyl group, and R 71 , R 72 , and R 73and cannot simultaneously be hydrogen atoms.
[0051] Exemplarily, the compound represented by formula (IC) may be one of the compounds represented by formulas (I-C1) to (I-C3). [ka]
[0052] In some further embodiments, the compound of formula (I) can include a compound of formula (ID): [ka] Here, R 71 is selected from a hydrogen atom, a halogen atom, and a C1-C2 alkyl group.
[0053] Exemplarily, the compound represented by formula (ID) may be a compound represented by formula (I-D1). [ka]
[0054] In some further embodiments, the compound of formula (I) can include a compound of formula (IE): [ka] Here, R 71 is selected from a hydrogen atom, a halogen atom, and a C1-C2 alkyl group.
[0055] Exemplarily, the compound represented by formula (IE) may be a compound represented by formula (I-E1). [ka]
[0056] In some embodiments, based on the mass n of the electrolyte, the mass of 1,3-propane sultone is A1, and the mass A1 of 1,3-propane sultone and the mass A2 of the compound represented by formula (I) satisfy 0.5≦A2 / A1≦8.0, or further 0.5≦A2 / A1≦8.0. By adjusting the masses of 1,3-propane sultone and the compound represented by formula (I) so as to satisfy the above content range, it is possible to further increase the stability of film formation and to increase the cycle stability of the lithium ion battery 1. In addition, it is also possible to maintain the cycle stability of the lithium ion battery 1 while reducing the amount of 1,3-propane sultone used.
[0057] In some embodiments, the mass n of the electrolyte and the mass m of the lithium ion battery 1 satisfy 7%≦n / m≦15%, and further 10≦n / m≦15. Based on the mass n of the electrolyte, the mass of the 1,3-propane sultone is A1, and the mass A1 of the 1,3-propane sultone and the mass m of the lithium ion battery 1 satisfy 0.01%≦A1 / m≦0.1%. The mass n of the electrolyte and the mass A1 of the 1,3-propane sultone in the electrolyte are adjusted according to the mass m of the lithium ion battery 1, thereby enhancing the film-forming effect of 1,3-propane sultone on the surface of the positive electrode active material. In this specification, n / m can be an electrolyte retention coefficient.
[0058] In order to improve the electrochemical properties of the lithium ion battery 1, in some embodiments, the electrolyte further comprises a carboxylate-based additive. Based on the mass n of the electrolyte, the mass percentage y of the carboxylate-based additive is 5%≦y≦60%, and the mass percentage y of the carboxylate-based additive, the mass A1 of the 1,3-propane sultone, and the mass A2 of the compound represented by formula (I) satisfy 0.05≦(A1+A2) / (n×y)≦0.6, and further 0.1≦(A1+A2) / (n×y)≦0.3. During the charge / discharge cycle of the lithium ion battery 1, the carboxylate-based additive can ensure the transport of metal ions, thereby improving the cycle characteristics of the lithium ion battery 1. In addition, the amounts of the carboxylate-based additive, the 1,3-propane sultone, and the compound represented by formula (I) used can be synergistically adjusted to satisfy the above ranges, thereby further improving the cycle characteristics of the lithium ion battery 1.
[0059] Exemplary carboxylic acid ester additives include one or more of ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate, butyl propionate, ethyl difluoroacetate, and ethyl trifluoroacetate.
[0060] During the charge / discharge cycle, the negative electrode active material contained in the lithium ion battery 1 may cause a side reaction with the electrolyte, which may reduce the electrochemical characteristics of the lithium ion battery 1. In order to further improve the electrochemical characteristics of the lithium ion battery 1, in some embodiments, the electrolyte further contains a carbonate-based additive. The carbonate-based additive is used to cause a polymerization reaction or a decomposition reaction during charging and discharging of the lithium ion battery 1. Based on the mass n of the electrolyte, the mass percentage z of the carbonate-based additive is 0.5%≦z≦15%, and the mass percentage z of the carbonate-based additive, the mass A1 of the 1,3-propane sultone, and the mass A2 of the compound represented by formula (I) satisfy 0.1≦(A1+A2) / (n×z)≦7, and optionally satisfy 0.2≦(A1+A2) / (n×z)≦1.1. During the charge and discharge process of the lithium ion battery 1, the carbonate ester additive can form a solid electrolyte interphase (SEI) film on the surface of the negative electrode active material, thereby protecting the negative electrode active material. In addition, by synergistically adjusting the amounts of the carbonate ester additive, the mass A1 of 1,3-propane sultone, and the compound represented by formula (I), the cycle characteristics and storage characteristics of the lithium ion battery 1 can be improved.
[0061] Illustratively, carbonate-based additives include fluoroethylene carbonate (FEC) and / or vinylene carbonate (VC).
[0062] In some embodiments, the electrolyte further comprises a polynitrile additive. The polynitrile additive is used to form a complex reaction with the cations in the positive electrode active material during charging and discharging of the lithium ion battery 1. Based on the mass n of the electrolyte, the mass percentage r of the polynitrile additive is 0.1%≦r≦12%, and further 0.5%≦r≦8%. During the charging and discharging process of the lithium ion battery 1, the polynitrile additive can form a complex reaction with the positive electrode active material, thereby forming a film layer on the surface of the positive electrode active material, thereby providing further protection to the positive electrode active material. In addition, by synergistically adjusting the polynitrile additive to satisfy the above range, the cycle characteristics of the lithium ion battery 1 can be further improved.
[0063] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer is provided on the surface of the positive electrode current collector. The positive electrode current collector may be one commonly used in the art, including, but not limited to, aluminum foil or nickel foil. The positive electrode active material layer includes a positive electrode active material. Exemplarily, the positive electrode active material includes, but is not limited to, lithium cobalt oxide, lithium manganate, lithium nickel oxide, etc., and can be selected as needed. Lithium ions can be reversibly absorbed and released into the positive electrode active material.
[0064] In order to increase the bonding strength between the positive electrode active materials, in some embodiments, the positive electrode active material layer may further include a binder. This can bond adjacent positive electrode active materials and increase the bonding strength between the positive electrode active material layer and the positive electrode current collector. Exemplary binders include, but are not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethyleneoxy-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated (esterified) styrene butadiene rubber, epoxy resin, nylon, and the like.
[0065] In order to enhance the conductive ability of the positive electrode active material layer, in some embodiments, the positive electrode active material layer may further include a conductive agent. In some embodiments, in order to enhance the conductivity of the positive electrode active material layer, the conductive agent includes carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powders, metal fibers, etc., including copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.
[0066] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer is provided on the surface of the negative electrode current collector. The negative electrode current collector may be one commonly used in the art, including, but not limited to, copper foil, nickel foil, or titanium foil. The negative electrode active material layer includes a negative electrode active material. Exemplarily, the negative electrode active material includes, but is not limited to, a carbonaceous material, a silicon-based material, an alloy-based material, a lithium metal-containing composite oxide material, and the like. Non-limiting examples of carbonaceous materials include crystalline carbon, amorphous carbon, and mixtures thereof. The crystalline carbon may be natural graphite or artificial graphite in an irregular shape or in a sheet, flake, spherical, or fibrous form. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, and the like, and may be selected as needed. Examples of the negative electrode active material include natural graphite, artificial graphite, mesocarbon microbeads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, and lithium-ionized TiO2-Li4Ti5O with a spinel structure. 12 , or a Li-Al alloy. Lithium ions can be reversibly absorbed and released into and from the negative electrode active material.
[0067] In some embodiments, in addition to the negative electrode active material, the negative electrode active material layer further includes a binder and a conductive agent. The binder and conductive agent in the negative electrode may be the same as those described for the positive electrode active material layer, and will not be described in detail here.
[0068] In some embodiments, the separator includes a polymer or inorganic material that is stable against the electrolyte. The inorganic material can include inorganic ceramic particles. Exemplarily, the inorganic ceramic particles can include one or more combinations selected from the group consisting of alumina, silica, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. Exemplarily, the polymer material includes one or more of polyamide, polyacrylonitrile, acrylic acid ester polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene), or is one or more selected from the group consisting of them.
[0069] The negative electrode, separator, and positive electrode in the lithium ion battery 1 have a variety of structural forms, for example, the negative electrode, separator, and positive electrode are sequentially stacked to form a laminated sheet structure, or the negative electrode, separator, and positive electrode are wound to form a wound structure 13. Specifically, the negative electrode, separator, and positive electrode are wound along a winding direction to form the wound structure 13, and the wound structure 13 includes two end portions 131 facing each other along the winding direction, and a middle portion 132 located between the two end portions 131.
[0070] As shown in FIG. 1 and FIG. 2, in some embodiments, the lithium ion battery 1 further includes a case 12 and a connection layer 11. The electrolyte and the winding structure 13 are provided in the case 12, and the connection layer 11 includes a first surface and a second surface facing each other along its thickness direction, the first surface connects the intermediate portion 132 and the end portion 131 of the two ends 131 that is closer to the case 12, and the second surface connects to the case 12. The connection layer 11 connects the intermediate portion 132 and the end portion 131 of the two ends 131 that is closer to the case 12, and fixes the winding structure 13, thereby reducing the risk of unwinding or expansion of the winding structure 13 and reducing the risk of gas accumulation inside the winding body, and the gas is discharged from the lithium ion battery 1 in a timely manner, thereby improving the safety characteristics of the lithium ion battery 1. Furthermore, the connection layer connects the winding structure 13 and the case 12, thereby increasing the connection strength between the winding structure 13 and the case 12 and reducing the risk of the separator shrinking and the winding structure 13 slipping after the lithium ion battery 1 generates gas during high-temperature storage, thereby improving the structural stability of the lithium ion battery 1. Furthermore, the connection layer 11 connects the case 12 and the winding structure 13, and by blending one or more of a cyclic sulfonate ester, a carboxylate ester additive, a carbonate ester additive, and a polynitrile additive added to the electrolyte, the safety characteristics of the lithium ion battery 1 in intermittent cycles can be improved.
[0071] As some examples, the connection layer 11 can be a hot melt adhesive SIS layer, or a composite film layer including a hot melt adhesive layer. The composite film layer may be a layer in which a hot melt adhesive layer, a metal layer, and a hot melt adhesive layer are laminated in order along its thickness direction, or may be a multi-layer hot melt adhesive layer. For example, the material of the hot melt adhesive layer includes one or more of polyolefin, polyolefin copolymer, polyamide, polyurethane, and epoxy resin. For example, the polyolefin includes polyethylene and / or polypropylene. Exemplarily, the polyolefin copolymer includes one or more of ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, styrene-isoprene-styrene copolymer, styrene-butadiene-styrene copolymer, styrene-(ethylene-butylene)-styrene copolymer, and styrene-(ethylene-propylene)-styrene copolymer. The metal layer can be an aluminum layer, a magnesium layer, etc.
[0072] It should be understood that the lithium ion battery 1 of the present invention can include all kinds of primary or secondary batteries. In particular, the lithium ion battery 1 is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0073] The application of the lithium ion battery 1 of the present invention is not particularly limited, and it may be used for any application known in the prior art.
[0074] As shown in Fig. 3, the lithium ion battery 1 of the present invention can be used in an electronic device 10. Here, the electronic device 10 includes, but is not limited to, a notebook computer, a pen-input computer, a mobile computer, an electronic book player, a mobile phone, a portable facsimile, a portable copy machine, a portable printer, a stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini CD, a walkie-talkie, an electronic notebook, a calculator, a memory card, a portable tape recorder, a radio, a backup power source, a motor, an automobile, a motorcycle, a bicycle auxiliaries, a bicycle, a lighting device, a toy, a game machine, a clock, an electric tool, a flashlight, a camera, a large household storage battery, and a lithium ion capacitor.
[0075] The technical solution of the present invention is further described below by taking lithium ion battery as an example and giving comparative examples and examples, but the present invention is not limited thereto. Those skilled in the art should understand that the preparation methods described in the present invention are merely illustrative examples, and any modifications or equivalent replacements made without departing from the scope of the technical solution of the present invention are within the protection scope of the present invention.
[0076] Working Example Preparation of Li-ion batteries The positive electrode active materials in the examples and comparative examples were prepared into lithium ion full batteries by the following method.
[0077] (1) Preparation of positive electrode The positive electrode active material, lithium cobalt oxide (LiCoO2), the conductive agent, Super P, and the binder, polyvinylidene fluoride (PVDF), were mixed in a weight ratio of 97:1:2, N-methylpyrrolidone (NMP) was added, and the mixture was stirred uniformly using a vacuum blender to obtain a positive electrode slurry. The positive electrode slurry was evenly applied to the aluminum foil, which was the positive electrode current collector, and the aluminum foil was dried. It was then cold pressed, punched, cut, and vacuum dried to obtain a positive electrode.
[0078] (2) Preparation of negative electrode The negative electrode active material, artificial graphite, the thickener, sodium carboxymethylcellulose (CMC), and the binder, styrene butadiene rubber (SBR), were mixed in a weight ratio of 97:1:2, deionized water was added, and the negative electrode slurry was obtained using a vacuum blender. The negative electrode slurry was evenly applied to the negative electrode current collector, copper foil, which was then dried, cold pressed, punched, cut, and vacuum dried to obtain the negative electrode.
[0079] (3) Preparation of electrolyte In a glove box with a dry argon gas atmosphere, ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of 1:3:6, additives were added and dissolved, and the mixture was thoroughly stirred. LiPF6, which is a lithium salt, was then added and mixed uniformly to obtain an electrolyte. The concentration of LiPF6 was 1.20 mol / L. The specific types and contents of the additives used in the electrolyte are shown in Tables 1 to 5. In this case, wt% was a mass percentage calculated based on the total mass n of the electrolyte.
[0080] (4) Preparation of separator To prepare a coating layer slurry, boehmite and polyacrylic ester were mixed and dissolved in deionized water, and then the coating layer slurry was uniformly coated on both surfaces of the porous substrate by microgravure coating and dried to obtain the desired separator.
[0081] (5) Preparation of lithium-ion batteries The positive electrode, separator, and negative electrode were stacked in order so that the separator was interposed between the positive electrode and the negative electrode to play a role of isolation, and then wound and tab-welded to obtain a bare cell. The bare cell was placed in an aluminum plastic film exterior foil, and the prepared electrolyte was injected. The soft-packaged lithium-ion battery was obtained through processes such as vacuum sealing, standing, formation, molding, and capacity grading. This battery did not include a protective plate or a pack package.
[0082] Characteristic measurements (1) Method for measuring the mass of the electrolyte The battery was discharged at a constant current of 0.1C until it reached 2.8V, and the weight of the battery was measured and recorded as m. The battery was then disassembled, and the bare cell and aluminum plastic film exterior foil obtained by disassembly were quickly placed in high-purity acetonitrile (purity ≧99.9%) for extraction, and the supernatant obtained by extraction was measured by gas chromatography to obtain the relative content of each component in the electrolyte. The bare cell and aluminum plastic film exterior foil after extraction were dried in a vacuum oven, and the total mass was measured and recorded as m'. The mass n of the electrolyte was n=m-m', and the actual mass of each component in the battery was the product of n and the relative content of each component. For example, A1=n×(relative content of PS).
[0083] (2) Intermittent Cycle (ITC) Measurement of Lithium-ion Batteries The lithium ion battery was placed in a thermostatic box at 45°C and left to stand for 30 minutes. The lithium ion battery was then discharged at a current of 0.5C until it reached 3.0V, charged at a current of 1C until it reached 4.5V, and left to stand for 24 hours, which constituted one charge-discharge cycle. As described above, 50 charge-discharge cycles were performed. The initial discharge capacity was recorded as C, and the discharge capacity after 100 cycles was recorded as C', and the cycle capacity retention rate was calculated by the formula (C' / C) x 100%. The initial thickness of the lithium ion batteries in the Examples and Comparative Examples was measured with a micrometer and noted as η, and the thickness of the lithium ion batteries in the Examples and Comparative Examples after 50 charge-discharge cycles was measured with a micrometer and noted as η'. The thickness change rate of the lithium ion batteries was calculated using the formula (η' / η-1)×100%.
[0084] (3) High-temperature storage test of lithium-ion batteries The lithium-ion battery was left to stand for 5 minutes in a room temperature environment of 25°C, charged at 1C until the voltage reached 4.5V, then charged at a constant voltage of 0.05C, and left to stand for 30 minutes. The initial thickness of the battery was measured and recorded as η1. The lithium-ion battery was then stored in a high-temperature furnace at 60°C for 50 days, and the thickness of the battery was measured when the measurement was stopped and recorded as η1'. The thickness change rate of the lithium-ion battery was calculated using the formula (η1' / η1-1)×100%.
[0085] Characteristics measurement results
[0086] [Table 1]
[0087] As can be seen from the characteristic measurement results in Table 1, by adding PS to the electrolyte and controlling the proportion of PS in the lithium-ion battery, it is possible to improve the ITC capacity retention rate and the thickness increase rate.
[0088] Comparing Examples 1-1 to 1-3 with Comparative Examples 1-1 to 1-3, it can be seen that as the mass of the lithium ion battery increases, the electrolyte retention coefficient does not change, but the ITC capacity retention rate and the thickness increase rate significantly deteriorate. This is because as the mass of the lithium ion battery increases, the contact area between the positive electrode active material and the negative electrode active material and the electrolyte increases, the consumption reaction of active lithium in the ITC cycle deteriorates, and when the protection of the positive electrode is lost, the site where the gas generation reaction occurs increases.
[0089] Comparing Examples 1-4 to 1-9 with Example 1-2, it can be seen that when the electrolyte retention coefficient n / m increases, the ITC thickness increase is significantly worse, but if the electrolyte retention coefficient n / m is within a suitable range, the ITC capacity retention rate can be improved, and the optimal value is found to be 7% to 15%. This is because, when the electrolyte retention coefficient increases, the PS mass does not change, but the ethylene carbonate solvent, lithium hexafluorophosphate, etc. are involved in the film formation reaction, which can protect the structural stability of the negative electrode material to a certain extent and improve the capacity retention rate, but if the protection of the positive electrode is insufficient, the solvent undergoes a decomposition reaction, and the amount of electrolyte increases, which instead worsens gas generation and the absorption and release reaction of lithium ions. As can be seen from Examples 1-9 to 1-10, when the electrolyte retention coefficient n / m is more than 15%, even if PS is further increased, the effect is not very desirable.
[0090] Comparing Examples 1-11 to 1-15 with Example 1-2, it is found that PS has a good positive and negative electrode film-forming effect. However, due to regulatory restrictions, there is an upper limit to the proportion A1 / m of PS in the cell, which must be ≦0.1%, and therefore the ITC cannot be further improved by further increasing PS.
[0091] Comparing Examples 1-16 to 1-21 with Comparative Examples 1-1 to 1-3, it can be seen that when the battery mass is different, taking into account the statutory mass percentage restrictions, the absolute upper limit of the amount of PS used will differ, and the optimal value of the electrolyte retention coefficient may also change, but is basically distributed between 7% and 15%.
[0092] [Table 2]
[0093] As can be seen from the characteristic measurement results in Table 2, by adding the compound represented by formula (I) to the electrolyte and controlling the content to 5%≧A2 / n≧0.5%, it is possible to achieve both an improvement in the ITC capacity retention rate and an improvement in the thickness increase rate.
[0094] Comparing Comparative Examples 2-1 to 2-2 with Example 1-8, it is found that, compared with PS, the compound represented by formula (I) is involved in the formation of positive and negative electrodes and can suppress an increase in thickness.
[0095] Comparing Examples 2-1 to 2-21 with Example 1-8, it is found that the combined use of PS and the compound represented by formula (I) can further improve the ITC capacity retention rate and the thickness increase rate.
[0096] Comparing Examples 1-20 and 2-3 with Examples 2-22 to 2-25, it is found that when the battery mass is different, the optimum value of A2 / A1 may change, but it basically falls within the range of 0.5 to 8.0.
[0097] [Table 3]
[0098] Comparative Example 3-1 and Comparative Example 3-2 are comparative examples in this specification, but are provided for the convenience of comparison with other data in Table 3. Note that Comparative Example 3-1 and Comparative Example 3-2 are still within the scope of protection of the present invention.
[0099] As can be seen from the characteristic measurement results in Table 3, by introducing a carboxylate-based additive into the electrolyte and optimizing the amount of the carboxylate used in combination with PS and the compound represented by formula (I), it is possible to improve the ITC capacity retention rate and thickness increase rate within a certain range.
[0100] Compared with Example 2-9, Comparative Examples 3-1 and 3-2 are those in which a carboxylate-based additive is solely introduced, and when the amount of electrolyte retention is inappropriate, the ITC capacity retention rate or thickness increase rate worsens instead.
[0101] In comparison with Example 2-9, Comparative Example 3-3 introduces a carboxylate ester, but does not introduce a compound represented by formula (I), so that the ITC capacity retention rate is significantly worsened. Since the carboxylate ester additive has a lower viscosity than the carbonate ester, an appropriate amount of carboxylate is advantageous for the transport of lithium ions, and in particular, if the electrolyte retention amount is too high, the electrolyte viscosity is high, which reduces the risk of delay in the release reaction of lithium ions, accumulation on the surface of the active material, and irreversible reactions, thereby ensuring the capacity retention rate of the battery. However, since the chemical stability of the carboxylate ester itself in the positive and negative electrodes is insufficient, if the content of the carboxylate ester is too high, the consumption of active lithium in the repair of SEI and CEI is accelerated, and if the protection for the positive electrode is lost, it indirectly leads to gas generation due to decomposition of the solvent, so that the content of the carboxylate ester additive can be controlled within an appropriate range to reduce the risk of gas generation.
[0102] Compared to Example 2-9, in Examples 3-4, and 3-12 to 3-16, different carboxylates have different effects on the ITC and thickness increase rate. When compared at the same usage amounts, propyl propionate is more advantageous in terms of capacity retention rate, and ethyl difluoroacetate is more advantageous in terms of thickness increase rate, and the ITC characteristic index can be improved in a balanced manner in a diversified carboxylate solvent system (a mixture of multiple types of carboxylate additives).
[0103] Compared with Example 2-9, in Examples 3-1 to 3-18, the carboxylate additive is combined with PS and the compound represented by formula (I), and the range of the contents of these three must be controlled to 60%≧y≧5%, 0.05≦(A1+A2) / (n×y)≦0.6, preferably 0.1≦(A1+A2) / (n×y)≦0.3. If the content of the carboxylate additive is too low, it cannot provide a smooth lithium ion transport path, while if the content of the carboxylate additive is too high, the electrolyte protection for the positive electrode becomes insufficient, and the solvent is easily decomposed and consumed.
[0104] [Table 4-1] [Table 4-2]
[0105] Comparative Example 4-1 and Comparative Example 4-2 are comparative examples in this specification, but are provided for the convenience of comparison with other data in Table 4. Note that Comparative Example 4-1 and Comparative Example 4-2 are still within the scope of protection of the present invention.
[0106] As can be seen from the characteristic measurement results in Table 4, the ITC capacity retention rate and thickness increase rate can be improved within a certain range by introducing a carbonate-based additive into the electrolyte and optimizing the amount of the carbonate-based additive used in combination with PS and the compound represented by formula (I). The ITC can also be improved by introducing a polynitrile-based additive into the electrolyte and controlling the amount of the polynitrile-based additive used.
[0107] In comparison with Example 3-16, in Examples 4-1 to 4-10, the negative electrode film formation can be repaired by introducing a carbonate ester additive, and the ITC capacity retention rate can be improved by controlling the content of the carbonate ester additive in the range of 1% to 10%. Different carbonate ester additives, FEC and VC, have different optimal values, and when (A1+A2) / (n×z)≧0.2%, both can achieve an improvement in ITC.
[0108] Compared with Comparative Examples 4-1 to 4-3, in Example 4-10, there is an interaction between the electrolyte retention coefficient, PS, the compound represented by formula (I), and the carbonate-based additive. By adjusting their contents, the carbonate-based additive can repair the negative electrode film formation and improve the cycle characteristics of the lithium cobalt oxide battery, thereby bringing about beneficial effects on cycle and storage.
[0109] Compared to Example 3-16, in Examples 4-11 to 4-25, by introducing a polynitrile additive and controlling the content to 0.1% to 12%, ITC gas generation can be significantly improved without impairing the ITC capacity retention rate. The optimal value of different nitrile additives is different, but the preferred range is 0.5% to 8%. If the content of polynitrile is too low, the protection for the positive electrode becomes insufficient and ITC gas generation becomes significant. On the other hand, if the content of polynitrile is too high, the viscosity of the electrolyte is significantly reduced, which delays the release reaction of lithium ions and deteriorates the capacity retention rate. When compared at the same usage amount, the trinitrile system has a more significant improvement against ITC gas generation than the dinitrile system, and the deterioration of capacity when it is excessive is also serious.
[0110] In comparison with Example 3-16, in Examples 4-26 to 4-33, the electrolyte retention coefficient, PS, the compound represented by formula (I), the carbonate-based additive, and the nitrile-based additive have mutually inhibiting relationships in terms of characteristics. When the relationship 0.1≦(A1+A2) / (n×z)≦7 is satisfied, and PS satisfies the legal regulations, the ITC characteristics are all significantly improved compared to the comparative examples in Table 1. Here, preferably, the relationship 0.2≦(A1+A2) / (n×z)≦1.1 is satisfied.
[0111] [Table 5]
[0112] In Table 5, the negative electrode tail adhesive connects the end closest to the case to the middle of the negative electrode to reduce the risk of the bare cell rewinding after winding. The U-shaped adhesive bonds the bottom of the bare cell after winding to reduce the risk of a safety accident caused by the separator shrinking after high-temperature storage measurement and the positive and negative electrodes coming into contact. The SIS hot melt adhesive is a double-sided tape that acts as a connection layer to bond the bare cell to the case after winding.
[0113] As can be seen from the characteristic measurement results in Table 5, compared with Example 4-26, Examples 5-1 to 5-3 all used negative electrode tail part adhesives, and especially Example 5-3 also used SIS hot melt adhesive as a connection layer. The negative electrode tail part adhesive and SIS hot melt adhesive can reduce the shrinkage of the separator and the slippage of the bare cell after gas generation due to high temperature storage, and reduce the risk of serious safety accidents caused by gas expansion, leakage, combustion, etc. In addition, the combination of the design of the structure and the design of the electrolyte can enhance the safety characteristics of the battery in the intermittent cycle and achieve effects that cannot be obtained by simply adjusting the electrolyte additives and solvents.
[0114] Compared with Example 4-32, in the batteries of Examples 5-3 to 5-4, the increase in ITC thickness cannot be suppressed by simply adjusting the electrolyte additives and solvent, but the ITC characteristics can be further improved by combining the electrolyte design with the use of a U-shaped adhesive and a SIS hot melt adhesive.
[0115] Although exemplary embodiments have been described and illustrated, those skilled in the art should understand that the above-described embodiments are not to be construed as limiting the present invention, and that modifications, substitutions, and alterations to the embodiments are possible without departing from the spirit, principle, and scope of the present invention.
Claims
1. 1. A lithium ion battery, The lithium ion battery includes a negative electrode, a positive electrode, a separator, and an electrolyte solution; The positive electrode includes a positive electrode active material, The separator is provided between the negative electrode and the positive electrode, The electrolyte solution contains a cyclic sulfonate ester, The cyclic sulfonate ester includes 1,3-propane sultone and a compound represented by formula (I) other than 1,3-propane sultone, 【Chemistry 1】 In formula (I), R 11 is a substituted or unsubstituted C 1 -C 4 Alkylene groups, and substituted or unsubstituted C 2 -C 4 alkenylene groups, R 12 is a single covalent bond, a substituted or unsubstituted C 1 -C 2 Alkyleneoxy group, -O-, and -R 13 -SO 2 -R 14 - selected from R 13 is a substituted or unsubstituted C 1 -C 2 alkylene groups, R 14 is a single covalent bond, a substituted or unsubstituted C 1 -C 2 an alkylene group, and -O-; R 11 , R 12 , R 13 , and R 14 When at least one of the groups is substituted, the substituent is selected from the group consisting of C 1 -C 20 Alkyl group, C 6 -C 30 an aryl group, a halogen atom, or -CN; A lithium ion battery, wherein the content of the compound represented by formula (I) is A2%, based on the mass n of the electrolyte, and the value of A2 is in the range of 0.5 to 5.
2. The compound represented by formula (I) is a compound represented by formula (IA) or a compound represented by formula (IB), 【Chemistry 2】 Here, R 61 , R 62 , and R 63 are each independently a hydrogen atom, a halogen atom, or C 1 -C 2 alkyl groups, Optionally, the compound represented by formula (IA) is any one of the compounds represented by formulas (IA1) to (IA4), 【Chemistry 3】 Optionally, the compound represented by formula (IB) is a compound represented by formula (I-B1) or a compound represented by formula (I-B2): 【Chemistry 4】 2. The lithium ion battery of claim 1.
3. The compound represented by formula (I) is a compound represented by formula (IC), a compound represented by formula (ID), or a compound represented by formula (IE), 【Chemistry 5】 Here, R 71 , R 72 , and R 73 are each independently a hydrogen atom, a halogen atom, or C 1 -C 2 alkyl groups, and R 71 , R 72 , and R 73 is not simultaneously a hydrogen atom, Optionally, the compound represented by formula (IC) is one of the compounds represented by formulas (I-C1) to (I-C5), 【Chemistry 6】 Optionally, the compound represented by formula (ID) is a compound represented by formula (I-D1): 【Chemistry 7】 Optionally, the compound of formula (IE) is a compound of formula (IE1): 【Chemistry 8】 2. The lithium ion battery of claim 1.
4. 4. The lithium ion battery according to claim 1, wherein the mass of the 1,3-propane sultone is A1, and the mass A1 of the 1,3-propane sultone and the mass A2 of the compound represented by formula (I) satisfy 0.5≦A2 / A1≦8.0, based on the mass n of the electrolyte.
5. The mass n of the electrolyte and the mass m of the lithium ion battery satisfy 7%≦n / m≦15%, and optionally satisfy 10≦n / m≦15; 5. The lithium ion battery according to claim 1, wherein the mass of the 1,3-propane sultone is A1, and the mass A1 of the 1,3-propane sultone and the mass m of the lithium ion battery satisfy 0.01%≦A1 / m≦0.1%, based on the mass n of the electrolyte.
6. The electrolyte further comprises a carboxylic acid ester additive, 6. The lithium ion battery according to claim 1, wherein, based on a mass n of the electrolyte, a mass percentage y of the carboxylic acid ester additive is 5%≦y≦60%, and the mass percentage y of the carboxylic acid ester additive, a mass A1 of the 1,3-propane sultone, and a mass A2 of the compound represented by formula (I) satisfy 0.05≦(A1+A2) / (n×y)≦0.6, and optionally satisfy 0.1≦(A1+A2) / (n×y)≦0.
3.
7. 7. The lithium ion battery of claim 6, wherein the carboxylic acid ester additive comprises one or more of ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate, butyl propionate, ethyl difluoroacetate, and ethyl trifluoroacetate.
8. The electrolyte further contains a carbonate-based additive, The carbonate-based additive includes fluoroethylene carbonate and / or vinylene carbonate, 8. The lithium ion battery according to claim 1, wherein, based on a mass n of the electrolytic solution, a mass percentage z of the carbonate-based additive is 0.5%≦z≦15%, and the mass percentage z of the carbonate-based additive, a mass A1 of the 1,3-propane sultone, and a mass A2 of the compound represented by formula (I) satisfy 0.1≦(A1+A2) / (n×z)≦7, and optionally satisfy 0.2≦(A1+A2) / (n×z)≦1.
1.
9. The electrolyte further comprises a polynitrile additive, the polynitrile additive is used to undergo a complex reaction with a cation in the positive electrode active material during charging and discharging of the lithium ion battery; Based on the mass n of the electrolyte, the mass percentage r of the polynitrile additive is 0.1%≦r≦12%, optionally 0.5%≦r≦8%; The polynitrile additive comprises one or more of the compounds represented by formulas (II-1) to (II-4), 【Chemistry 9】 In formulas (II-1) to (II-4), R 21 is a substituted or unsubstituted C 1 -C 12 Alkylene groups, and substituted or unsubstituted C 1 -C 12 alkyleneoxy groups, R 31 , R 32 each independently represents a single covalent bond, and a substituted or unsubstituted C 1 -C 12 alkylene groups, R 41 , R 42 , and R 43 each independently represents a single covalent bond, a substituted or unsubstituted C 1 -C 12 Alkylene groups, and substituted or unsubstituted C 1 -C 12 alkyleneoxy groups, R 51 is a substituted or unsubstituted C 1 -C 12 Alkylene group, substituted or unsubstituted C 2 -C 12 Alkenylene group, substituted or unsubstituted C 6 -C 26 Arylene groups, and substituted or unsubstituted C 2 -C 12 heterocyclylene groups, Here, R 21 , R 31 , R 32 , R 41 , R 42 , R 43 , and R 51 The lithium ion battery according to any one of claims 1 to 8, wherein when at least one of is substituted, the substituent is a halogen atom.
10. the negative electrode, the separator, and the positive electrode are wound along a winding direction to form a wound structure, and the wound structure includes two end portions facing each other along the winding direction and a middle portion located between the two end portions; The lithium ion battery according to any one of claims 1 to 9, further comprising a case and a connection layer, the electrolyte and the winding structure being provided within the case, the connection layer including a first surface and a second surface facing each other along a thickness direction of the connection layer itself, the first surface connecting the intermediate portion and the one of the two ends that is closer to the case, and the second surface connecting to the case.
11. The connection layer is a hot melt adhesive layer or a composite film layer including a hot melt adhesive layer; Optionally, a material of the hot melt adhesive layer comprises one or more of polyolefin, polyolefin copolymer, polyamide, polyurethane, and epoxy resin; Further, optionally, the polyolefin comprises polyethylene and / or polypropylene; 11. The lithium ion battery of claim 10, wherein the polyolefin copolymer comprises one or more of an ethylene-propylene copolymer, an ethylene-vinyl acetate copolymer, an ethylene-vinyl alcohol copolymer, a styrene-isoprene-styrene copolymer, a styrene-butadiene-styrene copolymer, a styrene-(ethylene-butylene)-styrene copolymer, and a styrene-(ethylene-propylene)-styrene copolymer.
12. An electronic device comprising the lithium ion battery according to any one of claims 1 to 11.
Citation Information
Patent Citations
Electrochemical energy storage device
CN105449255A
Non-aqueous electrolyte for lithium secondary battery, and lithium secondary battery comprising same
CN109075386A
Electrolyte, electrochemical device, and electronic device
CN112724043A